Níveis de proteína bruta e balanço eletrolítico para frangos de corte - Navarini, Franciele Clenice (2009)
Four experiments were conducted to evaluate the effects of different electrolyte balance and crude protein in feed for broiler chickens Cobb male line reared in natural conditions of heat stress. In experiment 1, were used 880 chicks in the period from 1 to 7 days of age with an average weight of 52,00 grams. Being housed 22 chicks per experimental unit, comprising a density of 14.10 chicks.m-2 housed in 40 boxes were distributed in a completely randomized design with 8 treatments, five replications. In experiment 2, were used 800 chicks in the period from 8 to 21 days of age with an average weight of 160,00 grams. Being housed 20 chicks per experimental unit, comprising a density of 12.82 chicks.m-2. In experiment 3, were used 640 chicks in the period from 22 to 35 days of age with an average weight of 640 grams. Being housed 16 chicks per experimental unit, comprising a density of 10.25 chicks.m-2. In experiment 4, were used 480 chicks, with an average weight of 1,700 grams, the period from 36 to 42 days of age. Being housed 12 chicks per experimental unit, comprising a density of 7.69 chicks.m-2. The diets were formulated from corn, soybean meal and maize gluten to meet the nutritional requirements of chicks in all experiments, according to Rostagno et al. (2005), except for crude protein whose levels were calculated, considering the levels recommended reducing 5%, 10% and 15%, and two electrolyte balance (200 and 240 mEq.kg-1) in all experiments. The animals received water and food ad libitum. In all the experiments was evaluated zootechnical performance (average gain of weight, average consumption of feed, feed conversion and final weight), and developing bone (index Sedoor). The environmental conditions of the building were monitored six times a day to help the hygrometer, a black globe thermometer and the readings used to calculate the of Black Globe Temperature and Humidity Index (BGHI). During the experimental period, the values of temperature, relative humidity, temperature and black globe BGHI remained above the zone of thermo neutrality of broilers. For the variables of performance in all experiments, except for experiment 4, the chicks had greater weight gain and final weight with the balance of 240 mEq.kg-1. In all experiments, the chicks that received diets with reduced levels of CP showed lower performance on fed diets without reducing protein, independent of the BE. This result is most evident in the diet with a reduction of 15% CP. With regard to blood tests, as reduced levels of CP in the diet, also decreased the concentration of uric acid in serum (p <0.05). For the electrolyte balance of 200 mEq.kg-1 saw the highest amount of calcium in blood serum. The chicks had lower percentage of total protein in blood stock in the range of 240 mEq.kg-1, the average levels of total protein in blood that range from 2.36 (experiment 4) to 2.92 mg.dL-1 (experiment 2) and below 3.6 mg.dL-1, are considered normal. The concentrations of K +, Cl-(Experiment 4) were not influenced (p> 0.05) by treatments. In relation to the concentration of sodium at 21 days of age (Experiment 2), the reduction of diet crude protein decreased (p <0.05) the concentrations of this mineral in serum. This response, however, was not observed at 42 days of age (Experiment 4). For evaluation of bone development, only the levels of CP protein used in the experiment 3, linearly affect the rate of Seedor femur (P <0.05). The effect of GA on the levels of Seedor index was not significant (P <0.05) for all experiments. For chickens from 22 to 35 days of age, levels of CP in the diet caused a linear effect and decreasing the rate of Seedor femur. Only in experiment 1 the levels of protein PB used linearly influence the rate of Seedor tibia (P <0.05), with linear response decreasing. The reduction in the levels of CP in the diet, results in lower values for the index of Seedor by reducing the length and weight of the femur. In general the reduction of 0%, 5%, 10% and 15% crude protein of diet on the recommended per phase, associated with correction of electrolyte balance, was not beneficial in the environmental conditions studied